Decyzja klasyfikacyjna. Charakter prawny oraz tryby kontroli i weryfikacji - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Classification is the process of dividing convicts sentenced into groups according to certain criteria by directing them to the proper type of prison and imprisonment system and by their proper distribution within the prison.The aim of this treatment is to create the best possible conditions of working with convicts, to counteract the harmful effects of demoralized convicts on other inmates as well as to ensure personal safety. The article presents the basic legal problems in issuing and verifying the classifying decision.
Keywords: klasyfikacja skazanych; kara pozbawienia wolności; indywidualizacja; specjalne traktowanie skazanych